High-Intensity Interval Training in Normobaric Hypoxia Leads to Greater Body Fat Loss in Overweight/Obese Women than High-Intensity Interval Training in Normoxia - Camacho-Cardenosa, Alba; Camacho-Cardenosa, Marta; Burtscher, Martin; Martínez-Guardado, Ismael; Timon, Rafael; Brazo-Sayavera, Javier; Olcina, Guillermo (Frontiers in Physiology, 2018)
A moderate hypoxic stimulus is considered a promising therapeutic modality for several pathological states including obesity. There is scientific evidence suggesting that when hypoxia and physical activity are combined, they could provide benefits for the obese population. The aim of the present study was to investigate if exposure to hypoxia combined with two different protocols of high-intensity interval exercise in overweight/obese women was more effective compared with exercise in normoxia. Study participants included 82 overweight/obese women, who started a 12 week program of 36 sessions, and were randomly divided into four groups: (1) aerobic interval training in hypoxia (AitH; FiO2 = 17.2%; n = 13), (2) aerobic interval training in normoxia (AitN; n = 15), (3) sprint interval training in hypoxia (SitH; n = 15), and (4) sprint interval training in normoxia (SitN; n = 18). Body mass, body mass index, percentage of total fat mass, muscle mass, basal metabolic rate, fat and carbohydrate oxidation, and fat and carbohydrate energy were assessed. Outcomes were measured at baseline (T1), after 18 training sessions (T2), 7 days after the last session (T3), and 4 weeks after the last session (T4). The fat mass in the SitH group was significantly reduced compared with the SitN group from T1 to T3 (p < 0.05) and from T1 to T4 (p < 0.05) and muscle mass increased significantly from T1 to T4 (p < 0.05). Fat mass in the AitH group decreased significantly (p < 0.01) and muscle mass increased (p = 0.022) compared with the AitN group from T1 to T4. All training groups showed a reduction in the percentage of fat mass, with a statistically significant reduction in the hypoxia groups (p < 0.05). Muscle mass increased significantly in the hypoxia groups (p < 0.05), especially at T4. While fat oxidation tended to increase and oxidation of carbohydrates tended to decrease in both hypoxia groups, the tendency was reversed in the normoxia groups. Thus, high-intensity interval training under normobaric intermittent hypoxia for 12 weeks in overweight/obese women appears to be promising for reducing body fat content with a concomitant increase in muscle mass.